Intraocular Lens Opacification following Intracameral Injection of Recombinant Tissue Plasminogen Activator to Treat Inflammatory Membranes after Cataract Surgery - Simon S. M. Fung; Evripidis Sykakis; Niaz M. Islam; Hadi J. Zambarakji; Ramin Khoramnia; Gerd U. Auffarth; Dipak N. Parmar (Journal of Ophthalmology)
Purpose. To report 7 cases of intraocular lens (IOL) opacification following treatment of postoperative anterior chamber fibrin with recombinant tissue plasminogen activator (rtPA) after cataract surgery. Methods. Retrospective case series of 7 eyes in 7 patients who developed IOL opacification after receiving rtPA for anterior chamber inflammatory membrane formation resulting from phacoemulsification cataract surgery. Three explanted IOLs were investigated with light microscopy, histochemical analysis, scanning electron microscopy, and X-ray spectrometry. Results. All patients underwent uncomplicated cataract surgery and posterior chamber hydrophilic IOL implantation. Anterior chamber inflammatory membranes developed between 1 and 4 weeks of surgery and were treated with intracameral rtPA. IOL opacification was noted between 4 weeks and 6 years after rtPA treatment with reduced visual acuity, and IOL exchange was carried out in 3 patients. Light microscopy evaluation revealed diffuse fine granular deposits on the anterior surface/subsurface of IOL optic that stained positive for calcium salts. Scanning electron microscopy (SEM) and energy-dispersive X-ray spectrometry (EDS) confirmed the presence of calcium and phosphate on the IOL. Conclusions. Intracameral rtPA, though rapidly effective in the treatment of anterior chamber inflammatory membranes following cataract surgery, may be associated with IOL opacification.